Characterization of soil salinization in typical estuarine area of the Jiaozhou Bay, China. (February 2018) - Li, Qifei; Xi, Min; Wang, Qinggai; Kong, Fanlong; Li, Yue
Abstract: In this study, the characteristics of soil salinization and the effects of main land use/land cover and other factors in typical estuarine area of the Jiaozhou Bay are investigated. Soil samples were collected in the parallel coastal zone, vertical coastal zone and longitudinal profile depth in the area to determine the soil salt content. The correlation analysis and principal component analysis are used to address the general characteristics of soil salinization in the study area. In the horizontal direction, there are moderate salinization, severe salinization and saline soil state. The farther from the sea (within 1.1 km), the lower the soil salinization degree. In the direction of longitudinal profile depth, there are severe salinization and saline soil state, and the soil salt content is accumulated in the surface and bottom. The Na + and Cl − are the dominant cation and anion, respectively, the distributions of which are consistent with that of salt content. All the salinization indexes, except for soil pH, are of moderate/strong variability. The invasion of Spartina alterniflora results in the increase of soil salt content and salinization degree, the effects of which are mainly determined by the physiological characteristics and the growth years. The degree of soil salinization increased significantly in the aquaculture ponds, which is mainly caused by the use of chemicals. The correlation between soil salt content and Na +, Cl − is particularly significant. From the results of principal component analysis, Na +, Cl −, Ca 2+, Mg 2+ and SO4 2− could be used as main diagnostic factors for salinization in typical estuarine area of the Jiaozhou Bay. The effects of NaCl and sulfate on salt content further affect the degree of salinization in the estuarine area. Highlights: Soil salinization in three-direction of the estuarine area was analyzed. The effects of Spartina alterniflora and aquaculture ponds on soil salinization were explored. The correlations between salt ions and salt content were revealed. The main diagnostic factors of salinization were determined.